An optimal mix of solar PV, wind and hydro power for a low-carbon electricity supply in Brazil - Johannes Schmidt; Rafael Cancella; Amaro Olímpio Pereira Junior (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2014)
Brazil has to quickly expand its power generation capacities due to significant growth of demand. Government plans aim at adding hydropower capacities in Northern Brazil, additional to wind and thermal power generation capacities. However, new hydropower may affect environmentally and socially sensitive areas in the Amazon region negatively while thermal power generation produces greenhouse gas emissions. We therefore assess how future greenhouse gas emissions from electricity production in Brazil can be minimized by optimizing the daily dispatch of photovoltaic, wind, thermal, and hydropower plants. Using a simulation model, we additionally assess the risk of loss of load. Results indicate that at doubled demand, only 2% of total power production has to be provided by thermal power plants. Existing reservoirs of hydropower plants are sufficient to balance variations in renewable electricity supply at an optimal mix of around 37% of PV, 9% of wind, and 50% of hydropower generation. In a hydro-thermal only scenario, the risk of deficit increases tenfold, and thermal power production four-fold. A sensitivity analysis shows that the choice of meteorological data sets used for simulating renewable production affects the choice of locations for PV and wind power plants, but does not significantly change the mix of technologies.
Keywords: Q42; 330; Brazil; greenhouse gas emissions; photovoltaic; wind; optimization